2016
DOI: 10.1128/aac.00404-16
|View full text |Cite
|
Sign up to set email alerts
|

Clomipramine and Benznidazole Act Synergistically and Ameliorate the Outcome of Experimental Chagas Disease

Abstract: bChagas disease is an important public health problem in Latin America, and its treatment by chemotherapy with benznidazole (BZ) or nifurtimox remains unsatisfactory. In order to design new alternative strategies to improve the current etiological treatments, in the present work, we comprehensively evaluated the in vitro and in vivo anti-Trypanosoma cruzi effects of clomipramine (CMP) (a parasite-trypanothione reductase-specific inhibitor) combined with BZ. In vitro studies, carried out using a checkerboard te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 48 publications
1
22
1
Order By: Relevance
“…Clomipramine has been used previously in mice in different dosages to study conditions such as antinociception (0.5 mg/kg) 40 , Chagas disease (7.5 mg/kg) 41 , and neurotransmitter and histone deacetylase expression (50 mg/kg) 42 . In humans taking clomipramine as an antidepressant, mean serum levels after a mean daily intake of 127 ± 91 mg/d have been reported to be 122 ng/ml (387 nM, considering a molecular weight of 314.9) 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Clomipramine has been used previously in mice in different dosages to study conditions such as antinociception (0.5 mg/kg) 40 , Chagas disease (7.5 mg/kg) 41 , and neurotransmitter and histone deacetylase expression (50 mg/kg) 42 . In humans taking clomipramine as an antidepressant, mean serum levels after a mean daily intake of 127 ± 91 mg/d have been reported to be 122 ng/ml (387 nM, considering a molecular weight of 314.9) 17 .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that damage to β -adrenergic receptors is mediated by autoantibodies produced against T. cruzi antigens that exhibit molecular mimicry to heart molecules [ 84 , 85 ]. It is natural that reduction in receptor density from immunological attack is accompanied by a compensatory increase in the affinity of the remaining receptors [ 25 , 86 ]. This behavior represents an important adaptive and counterregulatory mechanism in the attempt to adjust the cardiac function and to resist organ parasitism [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, molecular modeling techniques showed that tricyclic drugs, in particular phenothiazine, contained some of the best-fitting probes at the active site of TR and could indeed inhibit the parasite's flavoenzymes [ 115 ]. Although there is evidence of parasitological cure after clomipramine and thioridazine administration in T. cruzi- infected mice [ 26 , 86 ], it is still debatable whether this effect is exclusively mediated by TR inhibition and induction of redox imbalance, or other alternative mechanisms. There is evidence that clomipramine and thioridazine also interact with membranes and their components, intracellular proteins, and dopaminergic receptors; inhibit Mg 2+ -dependent ATPase activity; present a strong anticalmodulin activity; induce condensation of cytoplasm organoids; and disrupt mitochondria as well as kinetoplasts [ 25 , 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…brucei [ 57 ], and T . cruzi [ 58 ]. Trypanothione reductase is a protein that is critical in the antioxidant response of T .…”
Section: Introductionmentioning
confidence: 99%
“…Trypanothione reductase is a protein that is critical in the antioxidant response of T . cruzi ; thus, oxidative stress, inflicted by benznidazole, may be intensified by an inhibited antioxidant response mediated by clomipramine [ 58 ]. The antipsychotic drug, prochlorperazine [ 59 ], and the antihistamine, chlorpheniramine [ 60 ], both potentiated chloroquine and mefloquine by binding parasite-specific efflux pumps and ATP-binding cassette (ABC) transporters in Plasmodium vivax [ 59 ] or P .…”
Section: Introductionmentioning
confidence: 99%